α-Glucosidase inhibitory properties of leaves and bark extracts of Curatella americana L. (Research, Society and Development, 2022)
In this article, we investigate the inhibitory activity of methanolic extracts of bark and leaves of Curatella americana L. against α-glucosidase. Furthermore, antioxidant activity was evaluated using DPPH and ABTS assays, and the interaction of the identified compound of the extracts and α-glucosidase was tested by molecular docking. The results show that C. americana has a strong inhibitory activity against α-glucosidase reaching an IC 50 value of 7.29 µg/ml and 7.26 µg/ml for the extracts of bark and leaves, respectively. The enzyme kinetics reveals a mixed competitive mechanism for the leaves extract and an uncompetitive type of inhibition for the bark extract. The results of the antioxidant activity showed that both extracts have great antioxidant capacity, with the leaves extract having a better performance. The identified compounds of the extracts have a high binding affinity to the enzyme. Therefore, the study showed that C. americana extracts have a great potential for the treatment of diabetes, possibly serving as a therapeutic option to treat postprandial hyperglycemia and prevent long-term pathologies associated with diabetes.